Proactive Career Behavior Among University Students: The Roles of Future Work Self-Salience, Gender, Internship Experience, and Academic Background - Apui, Intania Bungan; Rusdi, Ahmad (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2024)
The issue of rising unemployment rates is becoming increasingly concerning, compounded by findings that some university students exhibit low levels of proactive career behavior. This study therefore aims to examine whether future work self-salience (FWSS), gender, self-initiated internship experience, and academic background can significantly predict proactive career behavior (PCB). The study involved 309 final-year students from various universities in Indonesia, with data collected using purposive sampling. Multiple linear regression analysis was used to test the predictive capacity of predictors on PCB. The results indicate that FWSS significantly predicts PCB (B= 0.3174, p < 0.001), with a clear FWSS cut-off point (FWSS > 4.009137) for predicting high PCB scores. Self-initiated internship experience also contributes significantly to PCB (B= 0.1315, p= 0.01), while gender (B= −0.0441, p= 0.391) and academic background (B= 0.0218, p= 0.67) do not show significant contributions to PCB. These findings emphasize the important role of FWSS and self-initiated internship experience in enhancing proactive career behavior among final-year students.